1999
DOI: 10.1128/mcb.19.11.7651
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Cell Wall Integrity Mitogen-Activated Protein Kinase Pathway in Budding Yeast by the Protein Tyrosine Phosphatases Ptp2 and Ptp3

Abstract: Mitogen-activated protein kinases (MAPKs) are inactivated by dual-specificity and protein tyrosine phosphatases (PTPs) in yeasts. In Saccharomyces cerevisiae, two PTPs, Ptp2 and Ptp3, inactivate the MAPKs, Hog1 and Fus3, with different specificities. To further examine the functions and substrate specificities of Ptp2 and Ptp3, we tested whether they could inactivate a third MAPK, Mpk1, in the cell wall integrity pathway. In vivo and in vitro evidence indicates that both PTPs inactivate Mpk1, but Ptp2 is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
107
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 74 publications
4
107
3
2
Order By: Relevance
“…In yeast, consistent with its role in adaptation of the mating pathway, Msg5 transcription is up-regulated in response to pheromone treatment (14). Although the existence of adaptation in the cell integrity pathway has been reported in a particular background (9), in most of the strains the level of phosphorylated Slt2 remained high and does not decrease for several hours upon stim- ulation (15,36). The absence of an increase in MSG5 transcription following heat shock is consistent with the lack of a Msg5-mediated negative feedback mechanism in this signaling pathway.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In yeast, consistent with its role in adaptation of the mating pathway, Msg5 transcription is up-regulated in response to pheromone treatment (14). Although the existence of adaptation in the cell integrity pathway has been reported in a particular background (9), in most of the strains the level of phosphorylated Slt2 remained high and does not decrease for several hours upon stim- ulation (15,36). The absence of an increase in MSG5 transcription following heat shock is consistent with the lack of a Msg5-mediated negative feedback mechanism in this signaling pathway.…”
Section: Discussionmentioning
confidence: 61%
“…In all of the strains tested, the exploration of dual Slt2 phosphorylation before and during thermal treatment in a wild type and a msg5 strain revealed that Msg5 played a fundamental role in down-regulating the basal activity of Slt2. The absence of either Ptp2 or Ptp3 does not lead to a significant increase in the amount of basal dually phosphorylated Slt2 (9,16). Furthermore, the dual-specificity protein phosphatase Sdp1 does not seem to be involved in maintaining a low basal Slt2 phosphorylation (16).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Protein tyrosine phosphatases and dual specificity phosphatases are known to affect MAPKs activity in yeast. For instance, Ptp2 and Ptp3 affect localization of the Hog1 MAPK, but are also known to regulate Fus3 and Slt2 (Mattison & Ota, 2000;Mattison, Spencer, Kresge, Lee, & Ota, 1999;Zhan, Deschenes, & Guan, 1997). The upper part of the Ste/MAPK cascade is shared between the pseudohyphal/invasive growth pathway and the mating pheromone response pathway and Kss1, the MAPK of the pseudohyphae/invasive growth module, has been indicated as a bona fide component of the mating pathway (Breitkreutz & Tyers, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…( Mattison et al 1999). Based on the high levels of colony sporulation in the W303 strain background and the involvement of multiple components of the CWI pathway in this sporulation, the W303 background was used for all remaining experiments in this study.…”
mentioning
confidence: 99%